Serbian Civil Code in the history of Serbian law - Popović Dragoljub (Pravni Zapisi)
The Serbian Civil Code (SCC) of 1844, modelled after the Austrian General Civil Code (ABGB), was a reception of Austrian civil law in Serbia. While the SCC was in force the Serbian law was exposed to various foreign influences and subject to spontaneous reception of French legal doctrine. In Yugoslavia, the SCC was an element of cohesion. Since the ABGB was in force in the greatest part of the country, the similarities between the two codes facilitated trade. The socialist revolution abrogated the old law. However, the courts continued applying the provisions of the SCC that did not conflict with the revolutionary acquis. The case law based on the SCC never played an important role in legal developments. The SCC left its mark to legal history by adopting the Roman foundations of Austrian law, which made Serbia a country that belongs to the family of European continental law. The SCC is at the origin of many Serbian legal terms, while some of its provisions defy the passage of time.